Pelanggaran Netralitas ASN dan Optimalisasi Pencegahan Pelanggaran oleh Badan Pengawas Pemilihan Umum Kabupaten Sidoarjo pada Masa Pilkada 2024 - Putri, Rahma Farahdini; Arundinasari, Indira (IAI Nasional Laa Roiba Bogor, 2025)
This study investigates the occurrence of neutrality violations among civil servants (ASN) during the 2024 regional elections in Sidoarjo, as reported by the Election Supervisory Agency (Bawaslu).A mixed-method approach was employed to analyze 25 documented cases, highlighting violations such as campaign participation, social media misuse, and abuse of authority.Primary data were gathered through interviews and observations, while secondary data included official documents and prior research. The findings of this study illuminate systemic challenges that erode democratic integrity, underscoring the imperative for enhanced training, stricter enforcement, and reforms to uphold ASN neutrality. The study further emphasizes the significance of safeguarding public trust in democratic institutions.